THE IMPORTANCE OF NON-GOVERNMENTAL ORGANIZATIONS IN MAINTAINING SOCIAL STABILITY IN MONGOLIA - Baljinnyam Gungaa,; Mandalmaa Sereeter,; Bayarmaa Minyanov,; Batjargal Lkhagva, (International Journal of Innovative Technologies in Social Science, 2024)
The involvement of non-governmental organizations (NGOs) is crucial for social stability and can achieve high results at low costs. NGOs make significant contributions to social development in areas such as community engagement, human rights protection, education, environmental conservation, and social services. However, their activities face numerous challenges, necessitating effective strategies to overcome these obstacles and enhance their impact on social stability. To support and strengthen the importance and participation of NGOs in ensuring social stability in Mongolia, it is essential to emphasize social cooperation, government support, and public involvement. By analyzing the operational focus and current status of NGOs in Mongolia, we can identify and implement ways to improve their importance and contributions to social stability, which will serve as a foundation for the country’s internal security. The relationship between the government, businesses, and NGOs is interdependent, and when they work together effectively, the nation can achieve development. NGOs, established by citizens, contribute to building a culture of cooperation that empowers the country and is considered the third largest sector in social development. Thus, NGOs should operate with sustainable, consistent, and unified characteristics to positively impact social stability. Moving forward, it is crucial for government policies to facilitate the growth of civil society in Mongolia by ensuring equal participation and consultation in governance. This will enhance the capacity and stability of NGOs while increasing their benefits and development through support from national and local governments.